P135 A novel composite index for prognostic staging of COPD patients. (14th November 2013) - Boutou, AK; Nair, A; Sandhu, R; Zadeh, DD; Hansell, DM; Wells, AU; Polkey, MI; Hopkinson, NS
Abstract : Introduction: Chronic Obstructive Pulmonary Disease (COPD) is characterised by high morbidity and mortality. Whether thorax computed tomography (CT)-derived parameters and lung function measurements carry more prognostic information individually or as a composite index has not yet been investigated. Aim: a) to compare the prognostic value of CT-determined emphysema and PAAo ratio versus various lung function parameters in a general COPD population and b) to construct a composite index for prognostic staging of COPD patients. Material and Methods: Predictors of mortality were assessed in a consecutive COPD outpatient population whose thorax CT, spirometry, lung volumes and gas transfer data were all collected prospectively in a clinical database. Univariate and multivariate Cox proportional Hazard analysis models were used and Hazard Ratios (HR) with corresponding 95% Confidence Intervals (CI) were calculated. Survival data were available until April, 2013 Results: 169 patients were included (59.8% male, 61.1 years old). During the follow-up 20.1% died; mean survival was 115.4 months. Age (HR = 1.077; 95% Cl = 1.032–1.121) and emphysema score (ES) (HR = 1.033; 95% CI = 1.010–1.057) were the only independent predictors of mortality when ES was treated as continuous variable in the multivariate regression. No association was found between PAAo Ratio and survival. Further analysis indicated that the 55% threshold of ES could be used as optimal and the 30% and 65% thresholds as suboptimals for prognostic categorization of patients in "high" (ES≥65%), "low" (ES<30%) and "intermediate" risk (30%≥ES<65%) group. The TLC%predicted was the most discriminatory of all pulmonary function parameters, so its threshold of 143%, which corresponded to ES optimal threshold, was further applied for the construction of the index. The final composite index separated patients in "high" risk (ES≥65% or TLC>143% predicted for intermediate group) and "low" risk (ES<30% or TLC≤143% predicted for intermediate group) (Figure) and was more discriminatory (HR = 2.751; 95% CI = 1.272–5.951) than any of its individual components. Conclusion: Although ES is better correlated with mortality than any pulmonary function parameter, a composite ES-TLC index carries the most prognostic information for COPD patients.